2009
DOI: 10.4254/wjh.v1.i1.67
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis C virus and peripheral blood mononuclear cell reservoirs Patricia Baré

Abstract: The existence of hepatitis C virus (HCV) infection in extrahepatic sites has been widely demonstrated. Since peripheral blood mononuclear cells have been the most investigated, compelling evidence of an association with HCV has been shown. Different studies have revealed that HCV RNA can persist and replicate in immune cells but the relevance of its presence and persistence over time is still unknown. As the contribution of this extrahepatic reservoir could have several clinical implications in viral transmiss… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
20
0
5

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(25 citation statements)
references
References 59 publications
(58 reference statements)
0
20
0
5
Order By: Relevance
“…7 The spleen is considered as one of the extrahepatic reservoirs of HCV. 3,4 It was also found that the longitudinal diameter of the spleen, as measured by ultrasound, was higher in patients with chronic HCV-related hepatitis than in the healthy controls. 8 HBV has similar characteristics.…”
Section: Discussionmentioning
confidence: 88%
“…7 The spleen is considered as one of the extrahepatic reservoirs of HCV. 3,4 It was also found that the longitudinal diameter of the spleen, as measured by ultrasound, was higher in patients with chronic HCV-related hepatitis than in the healthy controls. 8 HBV has similar characteristics.…”
Section: Discussionmentioning
confidence: 88%
“…Extrahepatic replication of HCV has been reported in peripheral blood mononuclear cells (PBMCs)-including granulocytes, monocytes/ macrophages, dendritic cells, and B lymphocytes-as well as extrahepatic tissues [Laskus et al, 1997[Laskus et al, , 1998a[Laskus et al, ,b, 2000Maggi et al, 1997Maggi et al, , 1999Shimizu et al, 1997;Lerat et al, 1998;Navas et al, 1998;Okuda et al, 1999;Roque-Afonso et al, 1999;Caussin-Schwemling et al, 2001;Radkowski et al, 2002;Goutagny et al, 2003;Radkowski et al, 2004;Bartolomé et al, 2008]. Extrahepatic replication of HCV has important implications for transmission, disease progression, and treatment [Bare, 2009]. For instance, several studies detected HCV RNA in PBMCs without detection in the corresponding serum or liver [Saleh et al, 1994;Taliani et al, 1995;Mazur et al, 2001].…”
Section: Discussionmentioning
confidence: 99%
“…19 Thus, it is possible that HCV-mediated hepcidin modulation, fine-tuned by the crosstalk between the cell populations, may affect iron content in the co-cultured cells in such a way that intramacrophagic HCV replication and the establishment of a viral reservoir are promoted. Despite the fact that the very existence of long-term occult extra-hepatic HCV reservoirs is strongly debated, 44 they would explain several clinical manifestations of the disease, like HCV persistence and recurrence following treatment or liver transplantation. 40,45,[46][47][48][49] Due to their role in iron homeostasis, reticuloendothelial macrophages, including Kupffer cells, may be full of iron at any given time.…”
Section: Discussionmentioning
confidence: 99%